Communication skills to increase reading comprehension in students of the 3rd grade of primary school - Espinoza-Rivera, Maria Geisi (2022)
This study arose from the need to apply the Speaking, Listening, Reading and Writing (HAELE) program to increase reading comprehension in students. This program will improve communication skills in the third year of primary school in the Paimas Educational Center, Piura 2021. The Juan Velazco Alvarado Educational Complex participated as experimental group (GE) and the 15164 Jambur Educational Complex as control group (GC). The objective is to determine the effect of the HAELE program. Most of the students do not master basic communication skills and it is important to analyze this problem, since the results will be useful for the directors of the educational institutions to take measures. Two groups with 23 students each participated in this experimental research. The communication skills program was applied to the GE. The inferential results showed that the arithmetic mean of the SG increased 7.96 points; the CG increased 1.77 points.  The standard deviation of the GE decreased 0.91 points, but the CG increased 0.15 points. The significance level of the SG decreased 0.722 points; the CG increased 0.105 points. It was concluded that the experimental program increases, for example, reading comprehension in students. Consequently, it is proposed that the authorities of the "Núcleo Educativo Paimas" apply the HAELE program.